(untitled) (Indian Journal of Animal Production and Management, 2013)
The effect of different types of housing system in hot humid climate of Mumbai on physiological and behavioral responses of Osmanabadi goat kids were studied in the present investigation. Significantly higher standing time and lower sitting time were recorded in kids of loose housed than conventional housed kids. The time spent on rumination was significantly higher in loose housed kids compared to conventional house kids. The mean heart rate, respiration rate per min, and rectal temperature in conventional housed kids were significantly higher as compared to kids in loose house. Thus present study indicates that loose house in hot months with kaccha floor and plastic shed net roof provide more comfort to kids than conventional house with slatted floor and asbestos roof.